Illuminating big cat movements: does moonlight influence Jaguar space use in the southern Pantanal? - Costa dos Santos, Priscilla (2022)
In light of increasing levels of habitat loss and modification, knowledge on the environmental factors that influence space use by large carnivores emerges as crucial for effective conservation efforts. Despite a growing body of literature exploring moonlight influence on the activity of felid apex predators, its effects on jaguars (Panthera onca) remain largely understudied - including in the Brazilian Pantanal. This wetland is currently undergoing significant human-driven changes with the expansion of agricultural activities, and retaliatory killing of jaguars arises as one of the main threats to the species' persistence. Here we studied the influence of variation in nocturnal luminosity on jaguars' space use in the southern Pantanal. We analyzed GPS data of collared jaguars in fields potentially used as pastures considering the distance to the closest forest and luminosity in the context of low, medium and high moonlight intensities. We found that although jaguars tend to remain close to forest surroundings throughout the lunar cycle, they venture deeper in pastures under medium to high moonlight illumination. We suggest that jaguars' pasture use at our study site fits the predation risk hypothesis, where species at higher trophic levels tend to be more active with moonlight as it allows for greater predation success - especially considering that forest edges can provide shelter and facilitate stalking of cattle. Although we did not focus on predation success in our analysis, we recommend herds to be kept away from forest edges and the placement of physical barriers (e.g. fences) to prevent opportunistic jaguar attacks - especially on brighter nights.